Molecular epidemiology, antibiotic resistance profile and frequency of integron 1 and 2 in adherent-invasive Escherichia coli isolates of colorectal cancer patients - Heidari, Aida; Emami, Mohammad Hassan; Maghool, Fatemeh; Mohammadzadeh, Samane; Kadkhodaei Elyaderani, Parisa; Safari, Tahereh; Fahim, Alireza; Kamali Dolatabadi, Razie (Frontiers in Microbiology, 2024)
This study explores the prevalence of Adherent-invasive Escherichia coli (AIEC) in colorectal cancer (CRC) patients and investigates the potential of effective intracellular antibiotics as a therapeutic strategy for CRC patients with AIEC infections. Considering the pivotal role of integrons in bacterial antibiotic resistance, the frequency of class 1 and 2 integrons in AIEC isolated from CRC patients, in one of the referenced 3 gastroenterology clinics in Isfahan, Iran was examined. AIEC strains were isolated from the colorectal biopsies and their antimicrobial sensitivity was assessed using the disc diffusion method. Polymerase chain reaction (PCR) was employed to detect intl1 and intl2. The multilocus sequence typing (MLST) method was utilized to type 10 selected isolates. Of the 150 samples, 24 were identified as AIEC, with the highest number isolated from CRC2 (33.4%) and CRC1 (29.16%), and the least from the FH group (8.3%) and control group (12.5%). int1 in 79.2% and int2 in 45.8% of AIEC strains were found and 41.6% of strains had both integrons. AIEC isolates with int1 exhibited the highest sensitivity to trimethoprim-sulfamethoxazole (57.9%), while those with int2 showed the highest sensitivity to ciprofloxacin (63.6%). A significant association between resistance to rifampin and integron 2 presence in AIEC isolates was observed. Furthermore, a significant correlation between integron 1 presence, invasion, survival, and replication within macrophages in AIEC strains was identified. MLST analysis revealed ST131 from CC131 with integron 1 as the most common sequence type (ST). The emergence of such strains in CRC populations poses a serious public health threat. The distribution pattern of STs varied among studied groups, with pandemic STs highlighting the importance of examining and treating patients infected with these isolates. Comprehensive prospective clinical investigations are warranted to assess the prognostic value of detecting this pathovar in CRC and to evaluate therapeutic techniques targeting drug-resistant AIECs, such as phage therapy, bacteriocins, and anti-adhesion compounds, for CRC prevention and treatment.